2017
DOI: 10.1038/s41598-017-01856-4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Strong Link Between Smoking and Cancer Pathogenesis through DNA Methylation Analysis

Abstract: Smoking is a well-documented risk factor in various cancers, especially lung cancer. In the current study, we tested the hypothesis that abnormal DNAm loci associated with smoking are enriched in genes and pathways that convey a risk of cancer by determining whether smoking-related methylated genes led to enrichment in cancer-related pathways. We analyzed two sets of smoking-related methylated genes from 28 studies originating from blood and buccal samples. By analyzing 320 methylated genes from 26 studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 64 publications
7
53
0
Order By: Relevance
“…28 A recent report demonstrated that AhR ligands promote fibrosis in a mouse model of chronic pancreatitis. 29 …”
Section: Resultsmentioning
confidence: 99%
“…28 A recent report demonstrated that AhR ligands promote fibrosis in a mouse model of chronic pancreatitis. 29 …”
Section: Resultsmentioning
confidence: 99%
“…Tobacco smoking has been reported to induce epigenomic changes including DNA methylation variation (reviewed in 41 ). Smoking is a well characterized risk factor in cancer 42 and, as more recently discovered, in the aetiology of autoimmunity 43 . Although smoking-related X-linked DNA methylation sites have been discovered 44 , no previous studies, to our knowledge, have investigated the relationship between smoking and XCI patterns.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the top three smoking-related miRNAs (hsa-miR-7704, hsa-miR-3655 and hsa-miR-203-3p) showed a clear relationship between smoking-dose and expression levels, and the top five age-adjusted smoking related pathways are involved with smoking. For example, the cholinergic synapse pathway is associated with nicotine addiction 56 and the relaxin signaling pathway is disrupted by smoking 57 . Our results show that smoking-related pathway RNAs (e.g.…”
Section: Discussionmentioning
confidence: 99%